SAT0630 Sensitivity and Specificity 99mTc-Pertechnetate Hand Perfusion Scintigraphy in Patients with Raynaud's Phenomenon. (9th June 2015) - Pavlov-Dolijanovic, S.R.; Petrovic, N.; Vujasinovic Stupar, N.; Damjanov, N.; Radunovic, G.; Radnic-Zivanovic, T.; Simic-Pasalic, K.; Zugic, V.; Babic, D.; Sobic-Saranovic, D.; Artiko, V.
Abstract : Objectives: The aim of this study was to assess sensitivity and specificity of 99m Tc-pertechnetate hand perfusion scintigraphy in patients with Raynaud's phenomenon (RP). Methods: The study population consisted of 10 healthy individuals (mean age 57 years), 18 patients with primary RP (mean age 48 years) and 25 patients with secondary RP within systemic sclerosis (SSc) (mean age 54 years). Gamma-camera dynamic first-pass study during the first 60 sec and a static scintigraphy after 5 min were recorded following a bolus injection of 99m Tc-pertechnetate via a cubital vein. Regions of interest were drawn on the summed images around the fingers and the palmar region. The fingers-to-palm ratios were then calculated from the total counts inside these regions of interest separately for each hand. Results: The mean fingers-to-palm ratio for dynamic study (blood flow) was 0, 58±0, 19 for the healthy group, 0, 45±0, 18 for the primary RP and 0, 43±0, 21 for the SSc patients. The mean fingers-to-palm ratio for static study (blood pool) was 0, 44±0.06 for the healthy group, 0, 42±0, 06 for the primary RP and 0, 36±0, 07 for the SSc patients. Analysis of variance showed these differences to be significant (p=0.039 from blood flow and p=0, 004 from blood pool). The receiver operating characteristic curve showed sensitivity of 80% and a specificity of 60% when using cutoff values of 0.40 for blood flow and sensitivity of 72% and a specificity of 73% when using cutoff values of 0.40 for blood pool. Conclusions: Our method is able to differentiate between patients with normal and those with abnormal microcirculation of the hands. Dynamic study separates the healthy subjects from patients with RP, while static study separating primary from secondary RP. References: Csiki Z, Galuska L, Garai I, Szabό N, Varga J, András C, Zeher M. Raynaud's syndrome: comparison of late and early onset forms using hand perfusion scintigraphy. Rheumatol Int. 2006 Sep;26(11):1014-8. Csiki Z, Garai I, Varga J, Szücs G, Galajda Z, András C, Zeher M, Galuska L. Microcirculation of the fingers in Raynaud's syndrome: (99m)Tc-DTPA imaging. Nuklearmedizin. 2005 Feb;44(1):29-32. Disclosure of Interest: None declared